Associations between oral hygiene habits, diet, tobacco and alcohol and risk of oral cancer: A case–control study from India. (December 2017) - Gupta, Bhawna; Bray, Freddie; Kumar, Narinder; Johnson, Newell W
Graphical abstract: Highlights: Poor oral hygiene was associated with a significant risk of oral cancer. Observed increased risk of oral cancer with tobacco habit in the presence of poor oral hygiene as compared to never-chewers with poor oral hygiene. Consumption of green, yellow, cruciferous vegetables and citrus fruits were protective against incidence of cancer. Linear dose-response association was observed between oral cancer and chewing tobacco per day. Smoking greater than ten bidis/cigarettes per day and for a duration greater than twenty-five years elevated risk. Abstract: Objective: This study examines the association between the incidence of oral cancer in India and oral hygiene habits, diet, chewing and smoking tobacco, and drinking alcohol. We also assessed the effects of oral hygiene habits with oral cancer risk among chewers versus never chewers. Methods: A hospital-based case–control study was conducted in Pune, India, based on face-to-face interviews, anthropometry, and intra-oral examinations conducted for 187 oral cancer cases and 240 controls. Results: Poor oral hygiene score was associated with a significant risk of oral cancer (adjusted OR = 6.98; 95%CI 3.72–13.05). When stratified by tobacco-chewing habit, the poor oral hygiene score was a significant risk factor only among ever tobacco chewers (adjusted OR = 14.74; 95%CI 6.49–33.46) compared with never chewers (adjusted OR = 0.71; 95%CI 0.14–3.63). Dental check-ups only at the time of pain by ever-chewers with poor oral hygiene was associated with an elevated risk (adjusted OR = 4.22; 95%CI 2.44–7.29), while consumption of green, yellow, and cruciferous vegetables and citrus fruits was protective. A linear dose–response association was observed between oral cancer and chewing tobacco in terms of age at initiation, duration, and frequency of chewing per day (P < 0.001). Smoking more than 10 bidis/cigarettes per day (adjusted OR = 2.74; 95%CI 1.28–5.89) and for a duration >25 years (adjusted OR = 2.31; 95%CI 1.14–4.71) elevated the risk of oral cancer. Conclusion: Good oral hygiene habits – as characterized by healthy gums, brushing more than once daily, use of toothpaste, annual dental check-ups, and a minimal number of missing teeth – can reduce the risk of oral cancer significantly. In addition to refraining from chewing/smoking tobacco, a diet adequate in fruits and vegetables may protect against the disease.